Pengaruh kepemimpinan, Motivasi, Pelatihan dan Lingkungan Kerja Terhadap Kinerja Karyawan Pada Perusahaan Daerah Air Minum Kabupaten Gunung Kidul - Alief Indita Agustiyani (Solusi: Jurnal Kajian Ekonomi dan Bisnis, 2015)
Assumption from this research reflected in hypothesis that suspect that htere is a positive and significant influence from leadership, motivation, training, and workin environment to performance. For testing the validity from that hypothesis it's needed a related data from worker opinion about leadership, motivation, traing, working environment, and performance.Data explored based one judgemnet and worker opinion from 100 respondents. The result of regression analysis is meanwhile F is 8,873 with significant 0,00. R square is 0,806. So the variable can explained 80,6% to performance and the rest 19,4% can be explained the another variables. From the research it can be concluded that leadership, motivation, training and working environment have positive inlfuence to performance.